Auxetic elastomers: Mechanically programmable meta-elastomers with an unusual Poisson's ratio overcome the gauge limit of a capacitive type strain sensor. (September 2019) - Lee, Young-Joo; Lim, Seung-Min; Yi, Seol-Min; Lee, Jeong-Ho; Kang, Sung-gyu; Choi, Gwang-Mook; Han, Heung Nam; Sun, Jeong-Yun; Choi, In-Suk; Joo, Young-Chang
Abstract: How can we modulate the inherent Poisson's ratio value of soft elastomeric materials? The theoretical limit value of the Poisson's ratio of isotropic materials can be defined from −1 to 0.5 but elastomers generally take the Poisson's ratio of 0.5. Herein, we introduce and establish the concept of a mechanical meta elastomer called "auxetic elastomer". This is a continuum-solid elastomer having unique programmable elastic properties of Poisson's ratio that are beyond their conventional ranges, and include in-plane negative and out-of-plane high positive Poisson's ratios. Leveraging these unique deformation characteristics, we applied auxetic elastomers as a soft dielectric material for a highly stretchable capacitive-type strain sensor that overcomes the inherent performance limitations in terms of the low gauge factor.